EVALUATING UPTAKE TOWARDS WRITTEN CORRECTIVE FEEDBACK TO IMPROVE WRITING SKILLS - Maureen, Jessica Febrianti; Syamsi, Vera (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
This study evaluates the effectiveness of written corrective feedback (WCF) in higher education, specifically within a Composition II course. It aims to identify the most commonly used types of WCF, their acceptance by students, and their impact on writing improvement. Using content analysis, 88 instances of WCF from the first and second essay drafts of 18 students were categorized into four types according to Hattie and Timperley framework: feeding up at the task level, feeding back at the task level, feeding back at the process level, and feeding forward at the process level. Feeding forward at the process level was most prevalent (51%), followed by feeding up and feeding back at the process level (20.5% each), and feeding back at the task level (8%). Feeding up at the task level had the highest acceptance rate (89%). Conversely, feeding back at the task level and feeding back at the process level had moderate reception (57% and 56%), while feeding forward at the process level had a substantial acceptance rate (67%). The findings emphasize that clear, varied, and goal-oriented feedback enhances students’ engagement, self-regulation, and writing proficiency by addressing specific areas for improvement and guiding future development, ultimately fostering sustained academic growth.